Brachytherapy for radiotherapy‐resistant head and neck cancer: A review of a single center experience. (1st March 2016) - Hazkani, Inbal; Rabinovics, Naomi; Limon, Dror; Silvern, David; Koren, Sion; Hadar, Tuvia; Bachar, Gideon; Shpitzer, Thomas; Popovtzer, Aron
Abstract : Objectives/Hypothesis: Despite advances in radiotherapy and chemotherapy treatments for head and neck cancers, the local failure rate is high. In most radiotherapy‐resistant cases, surgery is performed; however, some cases are considered unresectable. No standard treatment for these situations has been established. In this study, we review our experience with brachytherapy (BT), which has a different biological mechanism than standard radiotherapy. Methods: All patients received prior radiation to the recurrence area. Median high‐dose radiation BT dose was 50 Gy, administered in 5 to 10 Gy fractions twice daily for 5 days. High‐dose radiation was given via four to 10 catheters inserted under local anesthesia (3 patients) or general anesthesia with preventive tracheostomy (10 patients). Results: Thirteen patients received BT from 2010 to 2014. Male:female ratio was 1.6:1, and median age was 66 years (range 23–89). Of those 13 patients, 10 patients were diagnosed with squamous cell carcinoma (SCC) of the oral cavity, two patients with SCC of the nasal mucosa, and one patient with eccrine duct carcinoma. Prior radiation dose ranged from 60 to 70 Gy. Local control was achieved in 11 of 13 patients; only 15.3% (2 of 13) had in‐field recurrence. Five patients developed local out‐of‐field recurrence, and two developed distant metastases. Five patients are alive with no evidence of disease. No major toxicities were encountered. Two patients had severe mucositis and recovered within several weeks. Conclusion: Brachytherapy for radiotherapy‐resistant head and neck cancers is feasible with minor adverse events, which enables good local control. However, many advanced head and neck cancers develop regional or distant metastases; therefore, additional treatment should be suggested. Level of Evidence: 4. Laryngoscope, 126:2246–2251, 2016